eHealth adoption factors in medical hospitals: A focus on the Netherlands - Marina Van Geenhuizen; Sander Faber (European Regional Science Association (ERSA), 2015)
The Netherlands can be seen as one of the best healthcare systems in Europe. However, ICT application in hospitals in this country is somewhat behind the Nordic countries, with many hospitals ?stuck? in the stage of search and ?being interested? without a subsequent move to testing and actual implementation. This situation contradicts the expected gains of ICT use in making healthcare more effective and efficient, and making it less expensive, and is difficult to understand given the fact that eHealth has been on the European Commission Information Society?s policy agenda for more than a decade. With respect to Europe, there is a considerable variability in adoption levels, with Nordic countries like Finland, Sweden, Denmark and Estonia at the highest level of adoption and countries in Eastern Europe and Greece staying behind at the lowest level. To better understand these differences, we develop a model of organizational adoption of ICT in hospitals and explore this model using a database of 30 hospitals in the Netherlands. Some of the factors in the model inhibit characteristics that could be different between countries, in terms of finance (budgets), overall ICT use and national culture. In the empirical part, we test the validity of some constructs and use structural equation modeling. Not surprisingly, size of the hospital plays a role, while organizational readiness and support of the top management of the hospital have an important influence as well, partially directly and indirectly. Outcomes of the analysis also include non-linear influences on adoption and potentially reversed causality in particular stages of the adoption process. The study provides the following new elements: a more detailed look at adoption (more stages compared to previous research), design and testing of various constructs concerning adoption, exploration of an extended TOE (technological, organizational and environmental) framework in a hospital setting, and use of a specific PLS-SEM to identify non-linear relations in a relatively small sample. The paper concludes with a summary of interpretations and with some suggestions for improvement of eHealth policies, given the influence of hospital size, organizational readiness and management support on ICT adoption, and a different national context within Europe.
Keywords: D83; I18; O32; 330; ICT; adoption; hospitals; readiness; management; The Netherlands; Europe